Therapeutic Potential of Curcumin and Novel Formulations in Psoriasis Treatment: Evidence and Future Prospects - Kantasa T; Yeerong K; Klinjan P; Na Takuathung M; Settakorn K; Chuamanochan M; Tovanabutra N; Ampasavate C; Koonrungsesomboon N (Drug Design, Development and Therapy, 2025)
Tattiya Kantasa,1,2,* Kankanit Yeerong,1,2,* Preeyaporn Klinjan,1,2 Mingkwan Na Takuathung,1,2 Kornvipa Settakorn,1,2 Mati Chuamanochan,3 Napatra Tovanabutra,3 Chadarat Ampasavate,4 Nut Koonrungsesomboon1,2 1Clinical Research Center for Food and Herbal Product Trials and Development (CR-FAH), Faculty of Medicine, Chiang Mai University, Chiang Mai, 50200, Thailand; 2Department of Pharmacology, Faculty of Medicine, Chiang Mai University, Chiang Mai, 50200, Thailand; 3Division of Dermatology, Department of Internal Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai 50200, Thailand; 4Department of Pharmaceutical Sciences, Faculty of Pharmacy, Chiang Mai University, Chiang Mai, 50200, Thailand*These authors contributed equally to this workCorrespondence: Nut Koonrungsesomboon, Department of Pharmacology, Faculty of Medicine, Chiang Mai University, 110 Intawaroros Road, Muang, Chiang Mai, 50200, Thailand, Tel +66-53-935353, Email nkoonrung@gmail.com, nut.koonrung@cmu.ac.thAbstract: Psoriasis is a chronic inflammatory skin disease characterized by thickened, erythematous, and scaly plaques that significantly impact patients’ quality of life. Although various treatments are available, they often cause adverse effects, prompting the exploration of alternative therapies. Curcumin, a bioactive compound in Curcuma longa Linn. (turmeric), has demonstrated potential benefits in managing psoriasis. This article aims to comprehensively evaluate the anti-psoriatic activity, efficacy, and safety profiles of curcumin and its novel formulations, as well as to discuss future directions for enhancing their use as an alternative treatment for psoriasis. Curcumin exerts its anti-psoriatic effects through multi-targeted actions, including inhibiting cell proliferation, inducing apoptosis, suppressing pro-inflammatory cytokines, and enhancing skin barrier proteins, thereby alleviating psoriasis lesions. However, both oral and topical curcumin formulations face challenges, such as low bioavailability and limited skin penetration, underscoring the need for novel formulations to improve therapeutic outcomes. Clinical findings suggest that oral curcumin may provide greater efficacy and better tolerance as an adjunctive therapy for moderate to severe psoriasis, while topical formulations may help reduce severity and improve well-being in mild to moderate cases. Overall, curcumin and its novel formulations show promise as therapeutic agents for psoriasis treatment. However, further research, particularly large-scale clinical trials, is essential to evaluate long-term efficacy and safety comprehensively. Keywords: curcumin, curcuma, psoriasis, herbal medicine, formulation